PIRATES OF AFRICA’S SOMALI COAST: ON TERRORISM’S BRINK? - Swart, Gerrie (Scientia Militaria - South African Journal of Military Studies, 2011)
This article will examine and evaluate the potential threat of maritime terrorism inAfrica, in particular the threat posed at present off the Somali coast. Africa’s porousborders have provided an ideal conduit for the export of terrorism on land, and nowits unguarded coastlines are a potential new thoroughfare for maritime terrorists tooperate at sea. In Africa, the threat to maritime security and the proliferating threatof ungoverned spaces have lethally combined to spawn the major threat of piracyand now also the potential threat of maritime terrorism off the insecure coastline ofSomalia. At the time of writing, the security threats and challenges posed by therapid proliferation of piracy remains, and have continued to be so throughout 2009.As of recent, maritime experts observe that the waters off the coast of Somalia andthe Gulf of Aden have emerged as the most dangerous zones for seafarers.